INTERPRETATION OF SYNONYMY IN UZBEK LINGUISTICS (American Journal of Interdisciplinary Research and Development, 2023)
The present paperconsiders the traditional and contemporary views on defining synonyms in Uzbek linguistics, wheredistinguishing the similarities and differences in semic analyses of the lexical meanings of synonyms worth special attention.